2019
DOI: 10.1097/bco.0000000000000751
|View full text |Cite
|
Sign up to set email alerts
|

Effect of chronic narcotic use on episode-of-care outcomes following primary anatomic total shoulder arthroplasty

Abstract: Background: Bundled-care payments for total shoulder arthroplasty (TSA) make early outcomes relevant because they typically are tied to a 90-day episode-of-care. The purpose of this study was to determine the effect of chronic preoperative narcotic use on early postoperative pain relief, narcotic use, length of hospital stay, readmissions, and complications in patients with primary TSA. Methods: Chronic narcotic use was defined as use of narcotic pain m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…Best et al found that preoperative opioid use is independently associated with significantly greater odds of 90-day readmission following primary TSA (OR 2.56, 95% CI: 1.99, 3.29, p < 0.001) and with an increase in hospital length of stay of 0.13 days ( p = 0.001). 30 On the other hand, Mayer et al 18 found that the differences in complication rates and readmission rates were not statistically significant, and no difference in length of stay between both groups was seen.…”
Section: Resultsmentioning
confidence: 95%
See 4 more Smart Citations
“…Best et al found that preoperative opioid use is independently associated with significantly greater odds of 90-day readmission following primary TSA (OR 2.56, 95% CI: 1.99, 3.29, p < 0.001) and with an increase in hospital length of stay of 0.13 days ( p = 0.001). 30 On the other hand, Mayer et al 18 found that the differences in complication rates and readmission rates were not statistically significant, and no difference in length of stay between both groups was seen.…”
Section: Resultsmentioning
confidence: 95%
“…Twenty-one studies which met all of the inclusion criteria and were included in the final qualitative synthesis (Figure 1). [15][16][17][18][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40] There was substantial agreement for both title and abstract screening (Cohen's kappa = 0.71) and full-text review (Cohen's kappa = 0.72).…”
Section: Study Characteristicsmentioning
confidence: 93%
See 3 more Smart Citations